2004
DOI: 10.1007/s00417-004-0899-6
|View full text |Cite
|
Sign up to set email alerts
|

Binocular summation in visual evoked cortical potential in patients who have significantly different P100 peak latencies in their two eyes

Abstract: Binocular summation of VECP is not present in ON cases with large differences in the peak latency between the two eyes even if they have good stereoacuity. Binocular summation may not be correlated with stereopsis in adults whose binocular function has already matured.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 9 publications
2
3
0
Order By: Relevance
“…In the present study, the highest BS was obtained for the greatest defocus and pupil size for the P100 amplitude component (1.40 [0.23]). This is in line with Mizota et al, 46 who also found a mean BS for the P100 peak time in normal patients of 1.05, and 1.30 for the P100 amplitude, thus showing a greater and partial BS for the VEP amplitudes. Similarly, Heravian‐Shandiz et al 47 found an increase of 27% in the mean binocular amplitude compared with the mean monocular finding, indicating partial positive BS under normal conditions.…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, the highest BS was obtained for the greatest defocus and pupil size for the P100 amplitude component (1.40 [0.23]). This is in line with Mizota et al, 46 who also found a mean BS for the P100 peak time in normal patients of 1.05, and 1.30 for the P100 amplitude, thus showing a greater and partial BS for the VEP amplitudes. Similarly, Heravian‐Shandiz et al 47 found an increase of 27% in the mean binocular amplitude compared with the mean monocular finding, indicating partial positive BS under normal conditions.…”
Section: Discussionsupporting
confidence: 91%
“…These values are comparable to the binocular summation reported for VEPs to a range of flash and pattern stimuli in adults and children with normal binocular vision [17][18][19][20][21]. Although binocular summation is usually expressed as the ratio of binocular amplitude to mean monocular amplitude, the VEP from a randomly selected eye, as in the present study, is not expected to differ significantly from the mean of both eyes.…”
Section: Discussionsupporting
confidence: 82%
“…Generally, stationary or pattern-reversal stimuli (Jakobsson & Lennerstrand, 1985;Johansson & Jakobsson, 1993, 2000Mizota et al, 2004;Sato et al, 2002;Schmeisser & Dawson, 1982;Spekreijse, van der Tweel, & Regan, 1972;Wijeakumar, Shahani, McCulloch, & Simpson, 2012;Zemon & Ratliff, 1982) have been used, and studies using VECPs elicited by transient flashes The implicit times of the N2 and P2 elicited by stimulation of the dominant eye are shorter than those elicited by stimulation of the nondominant eye but the difference was not significant. Right two columns: Comparisons of VECPs recorded after binocular stimuli between dominant and nondominant eyes.…”
Section: Discussionmentioning
confidence: 94%
“…Journal of Vision, 14(11):4, 1-9, http://www.journalofvision.org/content/14/11/4, doi:10.1167/14.11.4. Chao, 1995;Spekreijse, van der Tweel, & Regan, 1972) and patients (Lennerstrand, 1978;Levi & Manny, 1982;Mizota, Hoshino, Adachi-Usami, & Fijimoto, 2004). VECPs have been used to evaluate these signals objectively.…”
Section: Introductionmentioning
confidence: 99%